ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN MASALAH VOLUME BENDA PUTAR DITINJAU DARI ASPEK BERPIKIR KRITIS - Betty Kusumaningrum; Muhammad Irfan; Zainnur Wijayanto (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Students of mathematics education need to have a good understanding in solving integral calculus problems, but often have difficulty in understanding the subject material. The difficulties can be seen from the mistakes made by students when solving the problems. This article aims to analyze the errors of students in learning integral calculus especially in the subject of volume of the solid of revolution in terms of critical thinking aspects. This research is a qualitative descriptive study involving twenty-four of 6th-semester students of mathematics education at a private university in Yogyakarta. The research subjects were chosen purposively by considering: student errors in determining the volume of the solid of revolutions with integral techniques in terms of critical thinking aspect. The findings of this study indicate, student errors in determining the function of integrals, write down the rules of integral writing, misunderstanding in algebraic concepts, adding constants, write down limits and sigma notations, determine integration methods, determine boundaries integration, writing in integral sign, and error in determining the radius of the solid of revolution.